2014
DOI: 10.1002/ppsc.201400192
|View full text |Cite
|
Sign up to set email alerts
|

Future Perspectives Towards the Use of Nanomaterials for Smart Food Packaging and Quality Control

Abstract: In this Progress Report some recent trends and future perspectives towards the use of nanomaterials for smart food packaging and quality control of food are given. The examples and discussion are meant to illustrate the potential use of nanotechnology for food sustainability rather than to review the state of the art of nanomaterials in this area, which although expected to have a groundbreaking impact on food sustainability is still on an early stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 73 publications
0
20
0
Order By: Relevance
“…However, there is a trade‐off between the potential cost related to food waste and loss as well as safety issues (w/o SP) and the extra cost of adopting smart packages, that is, the manufacturing cost of SP. Sensors or smart labels are key elements in SP system to monitor the food quality or storage conditions or to determine the exterior environment of a packaged product (both for manufacturer and consumer needs) (Jiang et al., ; Neethirajan & Jayas, ; Wyser et al., ). Suitable techniques to fabricate these smart elements which are compatible for the current packaging standards need to be developed and improved to reduce the related manufacturing costs but at the same time, broaden their range of applications for various food products.…”
Section: Manufacturing Technologies and Cost For Spmentioning
confidence: 99%
“…However, there is a trade‐off between the potential cost related to food waste and loss as well as safety issues (w/o SP) and the extra cost of adopting smart packages, that is, the manufacturing cost of SP. Sensors or smart labels are key elements in SP system to monitor the food quality or storage conditions or to determine the exterior environment of a packaged product (both for manufacturer and consumer needs) (Jiang et al., ; Neethirajan & Jayas, ; Wyser et al., ). Suitable techniques to fabricate these smart elements which are compatible for the current packaging standards need to be developed and improved to reduce the related manufacturing costs but at the same time, broaden their range of applications for various food products.…”
Section: Manufacturing Technologies and Cost For Spmentioning
confidence: 99%
“…Numerous scientific studies have shown that the incorporation of nanomaterials in biodegradable food packaging can increase performance by improving the mechanical and thermal properties of the materials. Furthermore, nanomaterials can provide new properties, such as antimicrobial and antifungal activities, elimination of oxygen, enzyme immobilization and protection against degradation, hence contributing to better stability of the stored products (de Azeredo 2009;Peelman et al 2013;Rhim et al 2013;Reig et al 2014;Jiang et al 2015;Kuswandi 2016).…”
Section: Potential Of Nanotechnology In Aquaculturementioning
confidence: 99%
“…This functionality is enabling the development of novel intelligent packaging concepts, which can be in the form of sensors (bio or temperature), or nanomaterial-based 'intelligent' inks, which can be printed on labels or incorporated in coatings for food packaging. [85][86][87] Such labels could, for example, show the consumer that the product is safe to consume or that the package integrity has not been compromised in the supply chain. Other labels can determine the level of microbial activity in a package by indicating when the food starts deteriorating or can provide an indication of time-temperature exposure to indicate if the cold chain has been breached.…”
Section: Active Packagingmentioning
confidence: 99%